Estudo computacional das ligações e interações químicas em complexos constituídos por oxocarbonos, pseudo-oxocarbonos e esquaraínas com propriedades espectroscópicas, eletrônicas e ópticas - Silva, Éder Henrique da (2015)
The oxocarbons, pseudo-oxocarbons and squaraines have a wide range of important applications because of its spectroscopic characteristics. In addition, they play an important role in coordination chemistry due to their ability to form complexes with various metallic cations in supramolecular chemistry. In this study the structural effects, intermolecular forces, electronic properties and the nature of chemical bonds in molecules and complexes formed by oxocarbonos, pseudo-oxocarbons and esquaraines were studied in order to obtain a better understanding about the processes responsible for the properties of these materials. The computational calculations were performed with the use of DFT and ab initio methods in conjunction with effective core potentials (ECP) for the Cu(ll) ion. The nature of the chemical bonds was investigated using the QTAIM (Quantum Theory of Atoms in Molecules) theory. The changes in the aromaticity of the studied structures were evaluated by methods based on structural (HOMA - Harmonic Oscillator Model of Aromaticity) and magnetic parameters (NICS - Nucleus-independent chemical shifts).